Strategi Pemasaran Ekspor Buncis Kenya (Phaseolus vulgaris L) (Studi Kasus: Gapoktan Wargi Panggupay Kabupaten Bandung Barat) - Sohibul Wafa, Wildan; Sam'un, Mohamad; Nur'azkiya, Luthfi (Program Studi Agribisnis, Fakultas Pertanian, Universitas Singaperbangsa Karawang, 2023)
Gapoktan Wargi Panggupay is one of the farmer groups located in the Lembang District, West Bandung Regency, engaged in the field of agribusiness. This research is to identify internal and external factors that influence the export of green beans, formulate strategies that can be applied in export marketing strategies for green beans, as well as formulate priority strategies. This research was conducted from November to December 2022. The respondents involved in this research were the chairman of Gapoktan Wargi Panggupay, the chairman of farmer groups, export supervisors, and farmers. Data analysis in this research used IFAS matrix, EFAS matrix, Grand Strategy matrix, and SWOT. Respondent sampling method used in this research was purposive sampling. The results of the research showed the position of the grand strategy matrix in quadrant I with an IFAS score of 1.06, while the EFAS obtained a score of 0.71. SWOT analysis resulted in eight strategies for green bean export marketing. The formulation of alternative matrices resulted in new strategies, including improving the quality and quantity of Kenyan beans with a score of 1.64, and increasing the number of working partners with a score of 1.71. This research concludes that the potential to facilitate exports and enhance competitiveness effectively through cooperation with partners, thus meeting the increasing export demands and expanding the international market.